A study on the revitalization of american dream under the office terms of president Barack Obama = Nghiên cứu về sự hồi sinh của giấc mơ Mỹ dưới nhiệm kì của tổng thống Barack Obama - Đỗ, Thị Diệp (2020)
The American Dream is considered one of the highest ideal of American people. It is the Dream of equal opportunity for everyone in United States to attain better life. Originally, it was the dream of people coming to United States for religious freedom. Overtime, the coverage of American Dream has widened and changed as social context changed. Under the presidency of President George W. Bush, through his policies, President Bush degraded the American Dream. After him, President Barack Obama took the office and has fixed President Bush’s mistake to revitalize the American Dream. The research investigated three areas: healthcare, education and economy under the office terms of the two presidents and noted that the American Dream on healthcare, education and economy has been revitalized by President Barack Obama via his policies implemented to fix President Bush’s flaws